Assessing neuropsychological impairment using Reitan and Wolfson's screening battery - Preiss, J; Preiss, M (Archives of clinical neuropsychology, 2013)
The aim was to verify the applicability of Reitan and Wolfson's proposed neuropsychological screening battery for adults (2006, 2008) in the Czech population. The sample consisted of 70 participants aged 19-65 years, all of whom were examined using a screening method as well as the full Halstead-Reitan neuropsychological battery (HRNB). The correlation, logistic regression, ROC curve analysis, sensitivity and specificity, and positive and negative predictive values were all calculated. The Pearson correlation between the screening scale of neuropsychological deficit and the General Neuropsychological Deficit Scale (GNDS) from HRNB was 0.78 (p < .001). When optimal cut-off scores of 8 were utilized (in accordance with Horwitz, Lynch, McCaffrey, & Fisher in Screening for neuropsychological impairment using Reitan and Wolfsońs preliminary neuropsychological test battery. Archives of Clinical Neuropsychology, 23, 393-398, 2008, but different from Reitan, & Wolfson in The use of serial testing in evaluating the need for comprehensive neuropsychological testing of adults. Applied Neuropsychology, 15, 21-32, 2008), 78.6% of individuals were correctly classified having neuropsychological impairment or no impairment according to the GNDS. Our results confirm that this neuropsychological screening battery has good psychometric properties in the Czech population.
Keywords: Logistic Models; Male; kognitivní poruchy; Halstead–Reitan neuropsychological test battery (HRNB); ROC Curve; Česká republika; Adult; Aged; dospělí; mužské pohlaví; senioři; Neuropsychological impairment; logistické modely; Neuropsychological Tests; Czech Republic; lidé; ženské pohlaví; Humans; Cognition Disorders; Sensitivity and Specificity; senzitivita a specificita; Receiver-operating characteristic (ROC); prediktivní hodnota testů; neuropsychologické testy; Female; ROC křivka; lidé středního věku; Predictive Value of Tests; Screening battery; Middle Aged